Role of Free Radicals, Glutamate Toxicity, Glutathione Depletion in Apoptosis of Cochlear Hair Cells, Neuronal Cells among Patients with Sensorineural Hearing Loss - Udagatti, Vithal D.; Kumar, Rajendran Dinesh; Samorekar, Arjunsing Vijaysing; KR, Vaibhavi (Annals of Otology and Neurotology, 2020)
Introduction Hearing loss may lead to depression, decreased quality of life, reduced functional status and social isolation. The glutathione-S transferase (GSTS) is an antioxidant scavenging enzyme. Decreased glutathione and GSTS activity levels lead to an increase in susceptibility of hair-cell damage leading to sensorineural hearing loss. The cumulative effect of oxidative stress and mitochondrial damage by free radicals results in the mutation/deletion of deoxyribonucleic acid, leading to decline in mitochondrial function, which in turn plays an important role in inducing apoptosis of the cochlear cells. Other risk factors also include noise exposure, genetic predisposition, health comorbidities, ototoxic drugs, infections, and immune-mediated inflammation of auditory cells.Study Design Prospective, non-comparative, metacentric clinical study.Materials and Methods The study was carried out in 30 patients from 6/5/2016 to 10/1/2018. Total of 30 patients of sensorineural hearing loss were enrolled (17 males, 13 females). Clinical history, ENT examination, and audiogram were done, treatment duration of 8 weeks for each patient and followed up to 3 outpatient visits. The patient was administered rebamipide 100 mg, alpha lipoic acid 100 mg, and acetylcysteine 100 mg capsules twice a day for a total period of 8 weeks. Wherever giddiness was an added symptom, Cinnarizine 20mg with Diaminehydrate 40 mg combination twice a day was added up to complete relief of symptoms, thereafter once a day as maintenance dose over a period of 8 weeks. Wherever tinnitus was an added symptom, deflazacort 6 mg twice a day was added and tapered up to 1 month. If the symptom of tinnitus persisted, intratympanic steroid injection was given. During every visit, clinical assessment and audiogram were repeated.Results Our study demonstrated greater improvement in hearing at higher frequencies with 8 weeks of rebamipide 100 mg + alpha lipoic acid 100 mg + acetylcysteine 100 mg administration in 30 patients with twice-daily dosing.Conclusion Synthesis of free radicals in the inner ear may play an important part in the pathogenesis of sensory hearing loss. The combination of rebamipide 100 mg + alpha lipoic acid 100 mg + acetylcysteine 100 mg is effective prophylaxis in sensorineural hearing loss that addresses both factors of inhibiting the cochlear cell damage and enhancing cochlear cell preservation.
Keywords: presbyacusis; glutathione; sensorineural hearing loss; free radicals